Measurement of Glycosylated Hemoglobins in Black Diabetic Patients: A Note of Caution - Lederman, Michael M. (1983)
Inspection of chromatography columns used for measurement of glycosylated hemoglobins revealed that blood samples from certain black diabetic patients produced two residual hemoglobin bands after chromatography rather than one. The levels of glycosylated hemoglobin were significantly lower in these subjects than in other diabetics. Further investigation revealed that each of these subjects had the hemoglobin AS or AC phenotype. The presence of hemoglobin S or C appears to cause spuriously low levels of glycosylated hemoglobin as determined by ion exchange chromatography. Other means to assess diabetic control should be used for patients with these abnormal hemoglobins.